KEMAMPUAN SISWA MEMBACA AL-QURâAN DALAM MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 7 PAMEKASAN - Haris, H. Abd (Universitas Islam Madura, 2019)
The ability to read al-Qur'an especially for students in public schools (SMP) is very important in improving learning achievement in the field of Islamic education. Said to be important because al-Qur'an as one of the scope of Islamic religious education becomes the basic basis of Islamic religious education material. Departing from these problems, the problem to be answered in this research is how the ability and urgency of students in reading the Qur'an at SMP Negeri 7 Pamekasan, in order to be able to improve the achievements of Islamic religious education. This study aims to determine the ability of students in reading the Qur'an at SMP Negeri 7 Pamekasan in order to improve the achievements of Islamic religious education students at SMP Negeri 7 Pamekasan. From the results of research conducted it turns out that the ability of students of SMP Negeri 7 Pamekasan in reading the Qur'an is good enough.Keywords: Al-Qur'an Reading Ability, Learning Achievement